Online learning attitudes and basic computer literacy of teacher education students - Joel Cayabyab Ferrer; Joy C. Corres (Premiere Educandum : Jurnal Pendidikan Dasar dan Pembelajaran, 2022)
This study was conducted to evaluate the online learning attitudes and the basic computer literacy of the College of Teacher Education of the Ilocos Sur Polytechnic State College, Philippines during the school year 2021 - 2022. The descriptive survey method that employed inferential statistics with a self-constructed questionnaire as the data gathering instrument with a reliability coefficient of 0.83. Total enumeration was used with 351 respondents. The findings revealed that the majority are females, they are in their first year, pursuing a degree in secondary education, lived in rural areas, and belonged to low-income families. Most of them were using smartphones, prepaid cards for their internet subscription which they sometimes experienced high-frequency signals, and were very proficient in their basic computer literacy. Along with cognition, students often experienced difficulties focusing their minds. The main problems in affective were feelings of isolation and lack of interaction. The psychomotor attitudes arise from the elimination of the actual practice. The income of parents and the location of the residence are factors in online resources. The variables in the online resources can affect their attitudes toward learning.Keywords: Learning attitudes, Online resources, Computer literacy, Learning attitudes